Kesalahan Berbahasa Tataran Semantik Dalam Unggahan Akun Instragram - Annisa Heryani; Yufi Safwan Fajar; Rochmat Tri Sudrajat (Universitas Katolik Widya Karya Malang, 2023)
There are a lot of language errors on social media, especially Instagram. One of the language errors that are also often found is language errors in semantics. This study aims to find out the language errors at the semantic level contained in Instagram information posters uploaded by @infobandungbarat. @infobandungbarat is the place to provide information throughout West Bandung district with slogan info in the area. The research method used in this study is a descriptive qualitative method with the final result in the form of a narrative. Data collection techniques in this study consisted of: 1) reading techniques, 2) note-taking techniques, and 3) documentation techniques. Data validation in research uses validity and triangulation of data sources. So from the results of this study it can be concluded that there are ten data obtained and analyzed. Errors contained in the data consist of word errors, word shortages, or inappropriate word placement, causing semantic language errors. The results of the analysis show that: 1) there are 5 data placement errors, 2) there are 4 word errors in the missing data, and 3) there are 1 data word errors.